2020
DOI: 10.1155/2020/2417539
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Nasogallbladder Drainage Combined with Laparoscopic Surgery for Type I Mirizzi Syndrome with Acute Cholecystitis: A Case Series Report

Abstract: Objective. To investigate the safety and feasibility of endoscopic nasogallbladder drainage (ENGBD) combined with laparoscopic surgery for Mirizzi syndrome type I with acute cholecystitis. Methods. An analysis of 4 patients with type I Mirizzi syndrome with acute cholecystitis admitted to the First Hospital of Jilin University. Results. The patients underwent ENGBD, and laparoscopic surgery was evaluated postoperatively. All four patients successfully recovered from this combined surgical approach. Conclusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Out of 17 analyzed studies, 6 had zero conversion rate [6,[17][18][19][20][21]. In the analyzed literature, most common causes of conversion were unclear or abnormal anatomy and severe adhesions (conversion rate 25.5-67%) [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Out of 17 analyzed studies, 6 had zero conversion rate [6,[17][18][19][20][21]. In the analyzed literature, most common causes of conversion were unclear or abnormal anatomy and severe adhesions (conversion rate 25.5-67%) [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options such as stenting, nasobiliary drainage, or stone removal may also be performed during the procedure, helping to relieve obstruction preoperatively. 8 One study has demonstrated that pre-op stenting also aids in identifying the common bile duct during surgery in patients with abnormal Triangle of Calot and biliary tree anatomy. 3 Complications may arise from ERCP which include infection and (1.4%) and perforation (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“… 5 While the laparoscopic approach was avoided in the past due to high variability in the hepatobiliary anatomy seen in these patients leading to bile duct injury and high rates of conversion to open laparotomy, newer evidence suggests that the laparoscopic approach after ERCP identification and therapeutic management is a reliable option in patients with a pre-operative diagnosis. 7 , 8 , 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation